Effect of compression stockings on overnight rostral fluid shift and obstructive sleep apnea: A meta-analysis. Issue 5 (October 2021) - Liao, Wei-Chih; Hsin, Li-Jen; Li, Hsueh-Yu; Tsai, Ming-Shao; Tsai, Yao-Te; Yu, Chung-Chieh; Lee, Yi-Chan
Abstract: Objective: The overnight rostral fluid shift from the lower limbs is one of the causes of obstructive sleep apnea (OSA). Compression stockings (CS) prevent lower limb fluid retention and have been reported to decrease nighttime fluid shift. The aim of this study is to evaluate the effect of CS on fluid shift and the severity of OSA. Methods: A systematic literature search was performed in the PubMed, EMBASE and Cochrane Library databases. The data were analyzed using Comprehensive Meta-Analysis software (Version 3; Biostat, Englewood, NJ). Studies evaluating the effect of CS on the overnight fluid shift and OSA severity were included in the analysis. Results: A total of 4 studies were included in this meta-analysis. The pooled analysis showed that the apnea-hypopnea index (AHI) of the overall study group was significantly lower after using CS (SMD, -1.08; 95% CI, -1.49 to -0.67). Decreases in the AHI were also observed in the normal fluid status (SMD, -1.05; 95% CI, -1.73 to -0.37) and fluid overload status (SMD, -1.17; 95% CI, -1.76 to -0.58) populations. The overall study group had significant decreases in overnight changes in neck circumference (SMD, -1.05; 95% CI, -2.06 to -0.03) and leg fluid volume (SMD, -1.14; 95% CI, -1.88 to -0.41) after using CS. However, no significant differences in overnight changes in neck circumference and leg fluid volume were observed in normal fluid status patients. Conclusion: CS may help decrease overnight fluid shift and could be a treatment option for OSA.